Hybrid additive manufacturing of high-quality polyetheretherketone (PEEK) -Ag conformal circuits by a laser in-situ crystallisation assisted fused deposition modelling and laser micro-cladding technique - Shuhuan Zhang; Wuxia Bai; Li Meng; Pan Chen; Jinhang Wang; Kaiwen Wei; Beibei Zhu; Xiaoyan Zeng (Virtual and Physical Prototyping, 2025)
Hybrid additive manufacturing technology combining fused deposition modelling (FDM) and laser micro-cladding (LMC) shows significant advantages for achieving the integrated fabrication of three-dimensional conformal circuits. This study systematically investigated the control mechanisms of the formation quality of polyetheretherketone (PEEK)-Ag conformal electronics fabricated via FDM + LMC. The results revealed that laser irradiation during LMC induced the recrystallisation and volumetric shrinkage of PEEK, causing cracking of the Ag film, which significantly compromised its electrical performance and interfacial adhesion. To address these issues, this paper introduces a novel laser crystallisation method to the FDM + LMC process, in which a laser irradiation was conducted to heat the FDM-printed PEEK and modulate its crystallinity, to enhance its thermal stability during LMC processing. By optimising the laser crystallisation parameters, the crystallinity of PEEK increased from 9% to 35%, while the melting enthalpy quadrupled. As a result, crack-free Ag film with adhesion to substrate of 5B level and electrical resistivity of approximately 12.1 µΩ·cm was obtained on PEEK. On this basis, PEEK-based antennas were fabricated by the laser crystallisation assisted FDM + LMC hybrid additive manufacturing technology, the radiation performance results have verified the feasibility of this technology on the integrated fabrication of PEEK-based conformal circuits.